Bio control of Listeria monocytogenes and Quality Assessment of Vacuum Packed, Cooked Crab meat using Oregano oil - Tabinda Shabir (KUFOS, 2018)
Abstract- Crab, particularly blue swimming crab, nutritionally significant and rich seafood, and one of the major commercially important crabs is mostly found in the southwest part of India along the coasts of Tamil Nadu, Kerala and Karnataka and also throughout the Andaman Sea and the Gulf of Thailand. Being highly perishable seafood because of the enzymatic, oxidative and bacteriological spoilage, it becomes unacceptable to the consumers and ultimately leads to a huge economic loss in seafood industry. Also, crab meat, being a RTE food product should be free of foodborne pathogenic bacteria like L. monocytogenes as it is consumed as such by the Americans and Europeans. To combat the problems of quality loss and pathogenic contamination of this product as well as the growing awareness of the consumers against use of synthetic carcinogenic agents to prevent food, the modern society is turning towards ‘green’ consumerism. It has led to the use of natural antioxidative and antibacterial agents in the food to prevent the food from spoilage and at the same time make it free of disease causing microbes. Thus, plant essential oils are being used as they have strong antioxidant and antimicrobial properties. Hence, in this study, Oregano Essential oil, containing potent antioxidant and antimicrobial agents namely carvacrol and thymol was used to see its effect on the cooked crab meat in combination with the age old technology of vacuum packaging when stored at 4°C for 28 days. In addition, the antimicrobial assay to check the efficacy of the oil against L. monocytogenes was done by the disc diffusion method and minimum inhibitory concentration. The current study found promising results after evaluating the biochemical (TVB-N, TMA, FFA and PV), microbiological (TVC and enumeration on PALCAM for L. monocytogenes) and the sensory parameters of the crab meat under 6 different conditions – control (under aerobic storage in the absence of oregano essential oil), VP (packed under vacuum in the absence of oregano essential oil), VP+0.5%O (vacuum packed with 0.5% oregano oil), VP+1%O (vacuum packed with 1% oregano oil), A+L+O (aerobically packed inoculated sample with oregano oil) and V+L+O (vacuum packed inoculated sample with oregano oil). The study found that oregano oil possessed strong antioxidant and antimicrobial which retarded quality loss, maintained sensory quality compared to control group (p<0.05) in combination with vacuum packaging. A decrease in the count of L. monocytogenes in the samples showed that the RTE product can be combined with oregano oil in enough quantity to render it pathogenically safe to be consumed. The best results for all the parameters tested above were obtained for the sample with 1% oregano oil in combination with vacuum packaging (p<0.05) as the parameters never crossed the acceptability limit in the sample. It was followed by the sample with 0.5% oregano oil and vacuum packaging (p<0.05) whereas control deteriorated faster than all the other treatments (p<0.05). Also, it was observed that the samples containing oregano oil did not cross the sensory acceptable limit even after 28 days of chilled storage. Vacuum packaging alone was not enough to prevent quality loss of samples but when combined with oregano oil, the results were effective and thus, proved that combining of the aforementioned hurdles together extended the shelf-life of the product and maintained its sensory quality.